From molecules to frameworks: Variable dimensionality in the UO2(CH3COO)(2)center dot 2H(2)O/HF(aq)/piperazine system. Syntheses, structures, and characterization of zero-dimensional (C4N2H12)UO2F4 center dot 3H(2)O, one-dimensional (C4N2H12)(2)U2F12 center dot H2O, two-dimensional (C4N2H12)(2)(U2O4F5)(4)center dot 11H(2)O, and three-dimensional (C4N2H12)U2O4F6 - Walker, S; Halasyamani, P; Allen, S; O'Hare, D (1999)
The hydrothermal syntheses and structures of a new series of organically templated uranium materials are presented. The materials are found in the UO2(CH3COO)2 · 2H2O/HF((aq))/piperazine system and span the range of dimensionalities from molecular, zero-dimensional, (C4N2H12)UO2F4 · 3H2O (UFO-8a and -8b) through framework, three-dimensional, (C4N2H12)U2O4F6 (MUF-1). It is stressed that this multidimensional series is synthesized by utilizing the same template molecule. Stability regions, wherein pure phases are synthesized, have been determined and depicted graphically through composition space and prism diagrams. The diagrams have allowed us to rationalize the product formed on the basis of initial reagent concentrations. The reported materials have been characterized by single-crystal X-ray diffraction, thermogravimetric analysis, and infrared and Raman spectroscopy. The zero-dimensional, or molecular, phases, (C4N2H12)UO2F4 · 3H2O (UFO-8a and -8b), contain dimers of edge-shared [UO2F5] pentagonal bipyramids. The one-dimensional phase, (C4N2H12)2U2F12 · H2O (UFO-9), is built up from chains of uranium(IV), coordinated by eight fluorine atoms, whereas the two-dimensional compound, (C4N2H12)2(U2O4F5)4 · 11H2O(UFO-10), contains layers of fluorine bridged uranium(VI) pentagonal bipyramids. The framework material, (C4N2H12)U2O4F6 (MUF-1), is built up from edge-shared [UO2F5] dimers that are comer linked, forming three intersecting one-dimensional channels. MUF-1 also represents the first open-framework actinide material. In addition, the structural topologies of both UFO-10 and MUF-1 are completely unprecedented with respect to uranium materials.